2019
DOI: 10.3758/s13415-019-00690-7
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance versus reappraisal: Behavioral, autonomic, and neural effects

Abstract: Emotion regulation (ER) is an important skill for well-being. Cognitive reappraisal is a goal-oriented cognitive change strategy. Acceptance involves decentering from immediate habits of reactivity, observing moment-to-moment shifts in thoughts, emotions, and sensations. These two regulation strategies are thought to have different effects on emotion; however, no study has examined the differential effects of reappraisal and acceptance on behavioral, autonomic, and brain responses in the context of ideographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 45 publications
4
58
0
2
Order By: Relevance
“…In contrast, we observed tremendous variation in the quantification of the autonomic indices. For example, studies on skin conductance level during reappraisal assessed baseline activity during a neutral condition that included the presentation of neutral stimuli (Wolgast et al, 2011;Lohani and Isaacowitz, 2014), right before stimulus onset (e.g., Shiota and Levenson, 2009), right before instruction (Opitz et al, 2014), after instruction , or reported no baseline assessment (Goldin et al, 2019). These studies then either subtracted mean activity of the respective baseline from mean activity during the regulation period (e.g., Shiota and Levenson, 2009;Opitz et al, 2014), calculated raw means (Goldin et al, 2019), or area under the curve .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, we observed tremendous variation in the quantification of the autonomic indices. For example, studies on skin conductance level during reappraisal assessed baseline activity during a neutral condition that included the presentation of neutral stimuli (Wolgast et al, 2011;Lohani and Isaacowitz, 2014), right before stimulus onset (e.g., Shiota and Levenson, 2009), right before instruction (Opitz et al, 2014), after instruction , or reported no baseline assessment (Goldin et al, 2019). These studies then either subtracted mean activity of the respective baseline from mean activity during the regulation period (e.g., Shiota and Levenson, 2009;Opitz et al, 2014), calculated raw means (Goldin et al, 2019), or area under the curve .…”
Section: Discussionmentioning
confidence: 99%
“…When looking at individual psychophysiological measures, findings are mixed with respect to the effects of emotion regulation on autonomic physiology. Reappraisal instructions focusing on decreasing negative emotions compared to a control condition have been shown to have no effect on (Gross, 1998a;Kalisch et al, 2005;Goldin et al, 2019), increase (Sheppes et al, 2009;Lohani and Isaacowitz, 2014), or decrease ) skin conductance and to increase (Urry et al, 2006;van Reekum et al, 2007) or decrease (Bebko et al, 2011) pupil diameter. Contradictory patterns can also be found for suppression strategies.…”
Section: Psychophysiological Responses Of Emotions and Emotion Regulamentioning
confidence: 99%
“…It consists of a mental stance characterized by openness and a non-judgemental attitude towards on-going emotional experiences ( Grecucci et al. , 2015 ; Goldin et al. , 2019 ), without trying to control, change, suppress or avoid them.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, acceptance involves decentering from immediate, habitual reactivity, observing moment-to-moment transitions in thoughts, sensations, and emotions (48). LOC is involved in object perception (49) and SPC serves functions related primarily to somatosensory system, or tactile perception (50).…”
Section: Discussionmentioning
confidence: 99%